PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL MATERI TEKS HIKAYAT PADA PESERTA DIDIK KELAS X SMA - Wahyuni, Siti; Septiana, Ika; Rahayu, Winarni (Universitas Batanghari, 2024)
Learning text narratives are part of the curriculum for 10th-grade high school students. Most students show a lack of interest in this subject, primarily due to their difficulty in understanding the language used. The language in narrative texts is Malay, which contains many archaic words or terms that are no longer commonly used. Therefore, there is a need for a teaching method that makes it easier for students to comprehend narrative texts. In this research, a contextual learning model that relates the material to the students' daily lives was used to facilitate students' understanding of narrative texts. This teaching method employed a mixed-methods approach. Data sources were obtained from students who undertook the learning of analyzing the values contained in narrative texts through the contextual learning model. The data in this study were observations of the values achieved by the students. Based on the research, it was found that the use of a contextual learning model can facilitate students in analyzing the values contained in narrative texts. Furthermore, students are also able to relate the learning content to their daily experiences in their surrounding environment.